2023
DOI: 10.1186/s12931-023-02312-w
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota composition can reflect immune responses of latent tuberculosis infection in patients with poorly controlled diabetes

Abstract: Background Diabetes mellitus (DM) is a major risk factor for tuberculosis (TB). Evidence has linked the DM-related dysbiosis of gut microbiota to modifiable host immunity to Mycobacterium tuberculosis infection. However, the crosslinks between gut microbiota composition and immunological effects on the development of latent TB infection (LTBI) in DM patients remain uncertain. Methods We prospectively obtained stool, blood samples, and medical recor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…Furthermore, indole-3-carboxyaldehyde, a derivative of tryptophan derived from the gut microbiota, was found to suppress IL-6 cytokine production of murine macrophages in response to stimulation by Mtb 61 . Previous reports have also correlated the gut microbiome with host immune responses to Mtb infection 62 and NTM infection 63 . The alteration of indole-3-carboxyaldehyde in our study may be partially explained by the role of tryptophan metabolism mediated by gut microbiome in the immune responses to NTM infection and TB.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, indole-3-carboxyaldehyde, a derivative of tryptophan derived from the gut microbiota, was found to suppress IL-6 cytokine production of murine macrophages in response to stimulation by Mtb 61 . Previous reports have also correlated the gut microbiome with host immune responses to Mtb infection 62 and NTM infection 63 . The alteration of indole-3-carboxyaldehyde in our study may be partially explained by the role of tryptophan metabolism mediated by gut microbiome in the immune responses to NTM infection and TB.…”
Section: Discussionmentioning
confidence: 95%
“…However, it is comparatively understudied in latent TB. One study among individuals with poorly-controlled diabetes, showed LTBI-positives people to be Bacteroides-, Alistipes-, and Blautiaenriched compared to LTBI-negatives 7 .…”
Section: Introductionmentioning
confidence: 99%
“…However, it is comparatively understudied in latent TB. One study among individuals with poorly controlled diabetes showed LTBI-positive people to be Bacteroides -, Alistipes -, and Blautia -enriched compared to LTBI-negative people [ 9 ]. During LTBI infection, comparisons of TB cases, HIV-negative LTBI-positive individuals, and LTBI-negative and active TB gut microbiomes showed trends of changes in Bacteroides and Firmicutes; however, no significant difference was observed in the composition of the stool microbiota [ 10 ].…”
Section: Introductionmentioning
confidence: 99%